Specializing Within a Prelicensure Nursing Program: An Innovative Clinical Design. - Barnum, Leslie; Mutascio, Jennifer (Journal of Nursing Education, 2023)
Background: Traditionally, prelicensure nursing programs aim to give students exposure to several different populations in preparation for becoming a registered nurse. Those who begin a career in a specialty such as pediatrics have often had little exposure and experience with the aptitudes and knowledge needed to be workforce ready. Method: An innovative clinical cohort program was designed to prepare students better to graduate with a strong specialty foundation already established. Following the American Association of Colleges of Nursing recommendation to seek academic-practice partnerships, this cohort model was established between a university and freestanding children's hospital. Students enrolled in this program complete all required didactic and simulation coursework in the traditional curriculum. In addition, they participate in frequent clinical experiences at the children's hospital throughout the entire program. Results: Students graduating from this program have received adequate preparation to graduate, pass NCLEX, and are competent in all necessary general nursing principles. At the same time, they are well versed in pediatric nursing and comfortable caring for this specialty population. Conclusion: Prelicensure students can specialize in pediatrics while meeting all general requirements of a traditional Bachelor of Science in Nursing program. This novel clinical cohort design could serve as a model to change standard programming and better meet the needs of our practice partners. [J Nurs Educ. 2023;62(8):475–478.]